48=d+23

Simple and best practice solution for 48=d+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48=d+23 equation:


Simplifying
48 = d + 23

Reorder the terms:
48 = 23 + d

Solving
48 = 23 + d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
48 + -1d = 23 + d + -1d

Combine like terms: d + -1d = 0
48 + -1d = 23 + 0
48 + -1d = 23

Add '-48' to each side of the equation.
48 + -48 + -1d = 23 + -48

Combine like terms: 48 + -48 = 0
0 + -1d = 23 + -48
-1d = 23 + -48

Combine like terms: 23 + -48 = -25
-1d = -25

Divide each side by '-1'.
d = 25

Simplifying
d = 25

See similar equations:

| 2.4b=108 | | 14-3x=15x+5 | | 57.88+.11x=58.54 | | 7(d+8)=2(d-7)+5d | | w+-9=12 | | -3x+5=2x+-10 | | 6s+2=3s+20 | | 2x(2x+2)+(2x+2)= | | 3y=7x-2 | | 9c+0=18 | | 2(8+6x)=3(4x-5) | | 4*(3b+6x)= | | .45(24)+.05x=.15(18+x) | | 3x+6=8x-7 | | k+(-3)=-5 | | 2x^2+16x-1=0 | | 14(d+4)=4(d-7)+10d | | T+0.95=1.25 | | -2+w=-5 | | (5x-6)-(6x-4)=-(-4+4x)-4x+6 | | -13d-12=-2(d+6)-11d | | 2p-8=6 | | a-12=1 | | 3x+6(x-5)=3(x-6) | | 2c+3=19 | | 1+3x-9=4x-7 | | 5+5b=20 | | 5x=50+x^2 | | X+25=50+x^2 | | 9x-13=-103 | | 7(5x+9)+(x+9)4=12 | | 2n^2+3n-9= |

Equations solver categories